POLA AKTIVITAS SEHARI-HARI PADA PASIEN DEMENSIA DI INSTALASI RAWAT JALAN RS. BAPTIS KEDIRI - Sulistyarini, Tri; Ananta, Lutfi Akvian Widi; Wulan, Retno (Jurnal Penelitian STIKES Kediri, 2011)
abstract Â  backgorund : Dementia is an organic syndrome characterized by global gradual decline of higher mental functions without any disturbance of consciousness. Dementia is often encountered in the elderly. The perceived problem of dementia can interfere activities of daily living. Therefore our efforts as a nurse is able to provide services and care for the elderly in achieving the level of independence by providing motivation and giving activities that are carried out every day according to the ability of the elderly. Method : The design of this research was descriptive. Sampling method was total sampling. Samples were 15 respondents they were patients with dementia or care giver/family of dementia patients who took the patient to Outpatient Installation Kediri Baptist Hospital. The research data was taken by the interview. Conclusion : The result of the research indicated that activities of daily living in patients with dementia on the ability in bathing independently got 9 people (60%). The ability to dress independently got 9 people (60%). The ability go to the toilet independently got 10 people (66.7%). The ability to move independently got 11 people (73.3%). Continental fulfillment independently got 14 people (93.3%). The ability to eat independently got 14 people (93.3%). Instrumental ability got 10 people dependent (66.7%). Â  Keywords : activities of daily living, dementia